Vanesia (Saint-Jean-Poutge, Gers) : une mutatio aquitaine de l’Itinéraire de Bordeaux à Jérusalem - Fabien Colleoni (Gallia)
This article reports on the findings of the programmed excavation of the Vanesia relay station, established in the Baïse plain, after which it was named. It is also referred to in the Itinerarium Burdigalense, between Éauze and Auch, their principal towns. After tracing the history of the digs, the article describes the organisation of and evolution in roadside architecture, in particular from the end of the 1st century AD to the beginning of the 5th century. Principal buildings, adjacent courtyards, residential buildings, thermal baths, latrines, and porticos are subjected to a detailed examination. The reference to the site as a mutatio in the Itinerarium Burdigalense raises issues as to the function of this establishment, which was clearly focused on accommodating travellers. These were most probably officials in certain cases, and thus mandated for state transport (the cursus publicus), but primarily private travellers. To end with, the article highlights the existence of an architectural model that has rarely been evidenced by archaeology to date, but that was undeniably present in Gaul, in Aquitaine as well as in Narbonne and Belgium.